Analysis of the reallocation of time spent sitting, sleeping, and performing physical activities under negative self-rated heath of university students - da Silva Ferreira, Mariana; Neves Nunes, Sandra Adriana; Bosquiero Papini, Camila; Ferreira de Sousa, Thiago (O Mundo da Saúde, 2022)
The aim of this study was to examine the effect of isotemporal substitution of physical activity, sedentary, and sleep time in relation to negative self-rated health (SRH) in university students from a public university in the state of Minas Gerais, Brazil. A cross-sectional study was carried out, in which data were obtained via a questionnaire and the study’s outcome was the negative SRH. The time per day spent on physical activity, sitting, and sleeping were standardized by constants of 10, 30, and 60 minutes. The isotemporal substitution model was used through the estimation of the Odds Ratio via binary logistic regression. The significance level was 5%. A total of 1,110 students participated in this study. It was observed that replacing 10, 30, or 60 minutes per day of sitting time for the same amount of time in physical activity reduces the probability of negative SRH among university students. In general, greater probability of negative SRH were observed when replacing the same times of physical activity with sitting time. No association was observed with sleep time reallocation. It is concluded that replacing at least 10 minutes of sitting time with physical activity can progressively reduce chances of negative SRH among university students.